Estimate Broad of Natural Mineral Resources Area Lateritic Nickel Based of Image Analysis Satellite Landsat 7 Etm+ In District Laonti, Konawe Selatan, Province of Southeast Sulawesi - Putri, Sri Kandi; Nova, Sari; Lionar, Uun; Putra, Aprizon (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
Mineral exploration is one of the important activities to obtain location information about where the minerals are, but this exploration process takes years and costly especially when carried out over a wide area. Therefore through this study the application of Geographic Information Systems and Remote Sensing for mapping the distribution of potential mineral deposits of lateritic nickel (Ni) is tested. The method used is the analysis of digital data Landsat 7 ETM +. Rocessed image data by performing a technique sharpening contrast, filtering, creation of a composite image and image fusion. Image data processing is for the interpretation of visual straightness, limit unit morphology and the estimation of mineral lateritic nickel. The data as well as analysis techniques NDVI in order to obtain the pattern of vegetation density on the surface. The results showed that the presence of lateritic nickel mineral formed on ultramafic rocks undergoing the process of weathering and serpentinization. Characterized with the appearance of geological structures identified as robust and fault structures. Which are also represent on the remote sensing images as rectangular flow patterns.Ultramafic rocks are located in the morphological undulating hills. Vegetation is identified growing on ultramafic rocks are categorized as dense vegetation. Vegetation that grows in the form of a single tree with an average diameter ≤30 cm. result generating estimates of mineral potential areas of lateritic nickel has an area ranging 6.3 ha.